An Empirical Study of DDPG and PPO-Based Reinforcement Learning Algorithms for Autonomous Driving - Sanjna Siboo; Anushka Bhattacharyya; Rashmi Naveen Raj; S. H. Ashwin (IEEE Access, 2023)
Autonomous vehicles mitigate road accidents and provide safe transportation with a smooth traffic flow. They are expected to greatly improve the quality of the elderly or people with impairments by improving their mobility due to the ease of access to transportation. Autonomous vehicles sense the driving environment and navigate through it without human intervention. And, Deep Reinforcement Learning (DRL) is witnessed as a powerful machine learning solution to address a sequential decision problem in autonomous vehicles. The detailed state-of-the-art work in autonomous vehicles using DRL algorithms along with future research directions is discussed. Due to the high dimensional action space, two continuous action space DRL algorithms: Deterministic Policy Gradient (DDPG) and Proximal Policy Optimization (PPO) are chosen to address the complex autonomous driving problem. The proposed DDPG and PPO based decision-making models are trained and tested using the TORC simulator. Both the algorithms are trained for the same number of episodes for lane keeping as well as multi-agent collision avoidance scenarios. To the best of our knowledge, this is the first paper to present the comparative performance analysis of these two algorithms, and DDPG is found to perform better in terms of higher reward and faster convergence than PPO. Hence, DDPG is a suitable option in the design of a decision model for autonomous driving.